Community Participation through Village Tourism Development in Kampung Batik Semarang - Pasaribu, Rotumiar; Sulastri, Endang; Wastutiningsih, Sri Peni (Indonesian Journal of Advanced Research, 2025)
The purpose of this research is to explore community participation in the development of Kampung Batik Semarang as a rural tourism destination. This research uses an exploratory qualitative approach. Data collection techniques were carried out through interviews with 11 informants, observation, and documentation from March to July 2025. The Kampung Batik Semarang Tourism Awareness Group (Pokdarwis) is the main actor in mobilizing participation, facilitating communication, and sustaining tourism development. This study concludes that effective village tourism development requires a balance between external support and local autonomy, as well as strengthening democratic processes through bottom-up and horizontal communication models that will ensure a fair distribution of benefits. Pokdarwis in Kampung Batik Semarang shows that empowering the community as active agents in tourism makes a positive contribution, especially for economic and social well-being.